Status of IDH mutations in chondrosarcoma of the jaws. Issue 1 (January 2023) - You, Z.; Zhang, J.; Zhang, H.; Li, X.; Sun, Z.; Sun, L.
Abstract: The aim was to analyse the relationship between mutations of the isocitrate dehydrogenase gene ( IDH ) and clinical characteristics of chondrosarcoma of the jaw in order to provide new information on its molecular pathology. Tissue samples were collected from 25 patients diagnosed with chondrosarcoma of the jaw. IDH mutations were detected through polymerase chain reaction and direct sequencing. Clinicopathological data were analysed retrospectively. The study included 14 female and 11 male patients; the median patient age was 38 years. Sixteen patients had lesions in the mandible, while nine had lesions in the maxilla. The most common symptom reported was the presence of a painless, slowly enlarging mass with swelling, with or without numbness. Twenty-four patients received radical surgeries and one patient received chemoradiotherapy. The recurrence rate was 21.7%. No IDH mutation was found in any of the 25 samples. IDH mutation may not be a key event in the occurrence and development of chondrosarcoma of the jaw. However, for chondrosarcomas of a different nature and origin, the pathological significance of IDH mutation needs to be studied further.